Densidad, crecimiento y supervivencia de juveniles de Lyropecten (Nodipecten) nodosus (Pteroida: Pectinidae) en cultivo suspendido en el Golfo de Cariaco, Venezuela - Acosta, Vanessa (2000)
The effect of culture density on growth and survival of juveniles was studied in the scallop Lyropecten nodosus with intermediate hanging cultures in Golfo de Cariaco, Sucre state, Venezuela, from December 1993 to July 1994. Six spat-densities (7, 15, 30, 60, 125 and 250 scallops/nets) were evaluated. The initial shell height and dry mass tissue were 9.4 ± 0.18 mm and 0.007 ± 0.0026 g, respectively. The specimens were placed into pearl nets and suspended in a long line at 8 m depth. Growth patterns of somatic tissue were similar, but with different magnitudes and inverse proportionality to culture density. No effect of density was observed on survival. These results suggest that intraspecific competition of cultivated scallops cause stress, which affects growth but not survival. We suggest as strategy for the management of culture density, successive density reductions, to obtain in a six months culture (intermediate culture) specimens of 50 mm in shell height in order to start the final culture period.